High glucose induces autophagy of MC3T3-E1 cells via ROS-AKT-mTOR axis. (5th July 2016) - Wang, Xiaoju; Feng, Zhengping; Li, Jiling; Chen, Lixue; Tang, Weixue
Abstract: In the present study, we investigate the function of ROS-AKT-mTOR axis on the apoptosis, proliferation and autophagy of MC3T3-E1 cells, and the proliferation of MC3T3-E1 cells after autophagy inhibition under high glucose conditions. MC3T3-E1 cells cultured in vitro were divided into the following groups: normal control group, N-acetylcysteine (NAC) group, 11.0 mM high glucose group, 11.0 mM high glucose + NAC group, 22.0 mM high glucose group, 22.0 mM high glucose + NAC group, CQ group, 22.0 mM high glucose + CQ group, 3-MA group and 3-MA + 22.0 mM high glucose group. ROS production was measured by DCFH-DA fluorescent probe. Cell proliferation was measured by MTT assay. Cells in different groups were stained with Annexin V-FITC/PI, and then apoptosis rate was detected by flow cytometry. Nucleus morphology was observed under fluorescence microscope after being incubated with Honchest33258. Protein expression was measured using Western blotting and immunofluorescence. Cell apoptosis and proliferation in high glucose group were increased and decreased, respectively, in a dose-dependent manner. Autophagy was significantly induced in high glucose group, even though different concentration of glucose induced autophagy in different stages of autophagy. ROS production in MC3T3-E1 cells was remarkably increased in high glucose group, but not in a dose-dependent manner. NAC, as an antioxidant, reduced ROS production and ameliorated cell apoptosis, proliferation abnormity and autophagy caused by high glucose. Expression of p-AKT and p-mTOR proteins were dramatically decreased in high glucose group, and NAC reversed their expression. In addition, 3-MA, an inhibitor of autophagy, significantly decreased the proliferation of MC3T3-E1 cells. When cocultured with 22.0 mM glucose that induced autophagy, proliferation of MC3T3-E1 cells was not affected compared to 22.0 mM high glucose group. Our present findings reveal that high glucose affects apoptosis, proliferation and autophagy of MC3T3-E1 cells through ROS-AKT-mTOR axis. In addition, autophagy inhibition does not affect the proliferation of MC3T3-E1 cells under high glucose conditions. Highlights: High glucose induces autophagy of osteoblasts. Apoptosis and proliferation of osteoblasts are impaired under high glucose. ROS-AKT-mTOR axis plays an important role in function and autophagy of osteoblasts under high glucose.